2022
DOI: 10.3390/nu14194011
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Idiopathic Scoliosis and Body Mass? A Scoping Review

Abstract: The etiopathogenesis of idiopathic scoliosis remains unknown, although genetic or hereditary factors, neurological disorders, hormonal and metabolic dysfunctions, biomechanical factors, and environmental factors seem to be involved. Several studies have found that patients with scoliosis have common characteristics of taller stature, lower body mass index (BMI), and low systemic bone mass. We conducted a scoping review to analyze the association between idiopathic scoliosis and BMI. The search for articles was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Studies looking at conservative treatment outcomes also found inconsistent results; one found that overweight patients have greater curve progression despite treatment [ 9 ], one found that underweight patients had the highest risk of progressing to severe curves [ 10 ], one found that both high and low BMI were more likely to fail brace treatment than mid-BMI patients [ 11 ], and still another found no difference between overweight and normal weight patients [ 12 ]. Additionally, the biological mechanisms behind the relationship between BMI and AIS are largely unknown [ 16 ]. Previous literature includes hypothesized multifactorial mechanisms such as genetic, biomechanical, and environmental factors as well as hormonal and metabolic dysfunctions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at conservative treatment outcomes also found inconsistent results; one found that overweight patients have greater curve progression despite treatment [ 9 ], one found that underweight patients had the highest risk of progressing to severe curves [ 10 ], one found that both high and low BMI were more likely to fail brace treatment than mid-BMI patients [ 11 ], and still another found no difference between overweight and normal weight patients [ 12 ]. Additionally, the biological mechanisms behind the relationship between BMI and AIS are largely unknown [ 16 ]. Previous literature includes hypothesized multifactorial mechanisms such as genetic, biomechanical, and environmental factors as well as hormonal and metabolic dysfunctions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the biological mechanisms behind the relationship between BMI and AIS are largely unknown [ 16 ]. Previous literature includes hypothesized multifactorial mechanisms such as genetic, biomechanical, and environmental factors as well as hormonal and metabolic dysfunctions [ 16 ]. However, there remains considerable variability in the literature, and etiopathogenesis of AIS and the relationship and mechanism between BMI and progressive AIS that requires surgical intervention remain largely unknown [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there were numerous studies reports on the relationship between AIS and body mass [ 16 ]. However, few studies have reported the association between lean mass and AIS, and the conclusions of the available studies are still inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the etiology of AIS remains unclear [3]. Genetic issues such as heredity, as well as endocrine, body mass, practice of high risk sports, and postural problems have been considered possible causes of AIS [3,[6][7][8]. Nutrients such as vitamin D, calcium, and melatonin had also been reported to occur and progress the symptom of AIS [9].…”
Section: Introductionmentioning
confidence: 99%